Encyclopedia of Microbiology - Maczulak, Anne E (Viva Books, 2013)
Humans have always struggled with how to balance the benefits bacteria offer with the threats that they produce. Much less obvious than the effects microorganisms have on plants and animals are the indirect ways in which they shape the planet. These hidden activities have rarely been explained in science, though scientists realize that the behavior of microbes supports all life on Earth. In more than 200 entries, Encyclopedia of Microbiology presents the myriad ways in which microorganisms influence the biosphere. Focusing on how all microorganisms relate to each other just as all higher organ.